EVALUASI PROGRAM KESEHATAN LINGKUNGAN DI PUSKESMAS SIAK HULU II KABUPATEN KAMPAR TAHUN 2012 - Indawati ' Indawati; Thamrin ' Thamrin; Zainal Abidin (Jurnal Ilmu Lingkungan, 2014)
This research was conducted on March to August 2012, at Public Health Center of SiakHulu II Kampar regency. This study generally aims to evaluate the program of theenvironmental health at Public health center of Siak Hulu II Kampar regency in 2012,while the specific objectives are to evaluate the program landfills and waste andevaluate vector control programs in Public health center of Siak Hulu II Kamparregency. The method used in this research is a qualitative method. Analysis of the datausing content analysis to obtain in-depth information from informants about landfillsand waste and vector control to be made by noting the matrix and analysis manually.The results of program activities of landfills and waste at Public Health Center wasnot performing well and was not achieving the target set, where the environmentalhealth officers only surveyed garbage and waste in communities residential, whilemonitoring of garbage and waste in another place there has never been carried outsupervision and follow-up. In monitoring garbage and waste, due to limitedenvironmental health officer and far distance of coverage areas, health officerssupervise in line with the counting of numbers of the free larva, while the results of theVector Control Program for vector causing dengue fever can be accomplished inaccordance with procedures established by the Department of Health, but there areobstacles to doing fogging because Public health center firstly have to collect case ofEpidemiology investigation (PE) for a month and then report to the regency HealthOffice to conduct fogging while for vector types causes other diseases that are notcontrol ever only if there is a problem in the society so Public community health centerwill cooperate with existing cross sector of health center working area and doingoutreach to the community